The EFL Students' Viewpoints on the Contributing Critical Reading Strategies in Critical Reading Comprehension Class - Nurhayati, Dwi Astuti Wahyu (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Promoting critical thinking skills should more adapt to critical thinking strategies. The determined investigation aimed to pinpoint groups’ attention to the applying dominant popular Critical Reading Strategies, how to apply critical reading strategies (CRS), how to handle challenges and benefits in critical reading comprehension class. This investigation was disseminated by supervising interview and assigning survey to eighty-four pupils of UIN SATU Tulungagung who joined Critical Reading Comprehension Class by approving qualitative way. This study revealed that the Journaling rank first, Stop,Paraphrase, Questioning as well as Annotation and Marking the text as the second; but practicing several critical reading strategies frequently such as inferring, monitoring understanding, paraphrasing, critical lens, contrarian are desirable to boost students’ critical reading skill. Admitting of arising challenges, equally the capacity of analysing data, ascertaining writers' intentions; evaluating the author's arguments, they claim that their skill of learning critical reading comprehension are getting enhanced through applying suitable CSR practice deploying cognitive process, cultures and linguistic.